Culture-based economy of the border town: a case study of Tumpat, Kelantan - Yap, Sui Chai; Ng, Kah Choon (Penerbit Universiti Kebangsaan Malaysia, 2023)
A culture-based economy is a form of an economic sector that is particularly important in rural areas of many Southeast Asia countries. However, this industry has received limited attention within the research community. There are many culture-based economic sectors worldwide, but for this study, we focused on three main sectors, which are traditional food products, handicraft products, and cultural products. This study aimed to discover the factors and importance of these sectors in Tumpat, Kelantan. We conducted semi-constructed interviews with local entrepreneurs in the study area. Data were analyzed using the inductive content analysis method. We extracted the interview result based on two main categories: the factor of starting a business and the importance of the clustered pattern of culture-based business. The result demonstrated that the factors influencing business location in the study area were family heritage land, accessibility to resources, easiness of transportation, and readiness of potential workers. This study also revealed that these businesses were in the clustered pattern to reduce the production cost, share information and technology, and improve market size. The study provides an overview on the factors and significance of culture-based economic activities in Tumpat. Moreover, we also encourage more stakeholders to support and promote these culture-based economic activities in developing countries.